Repertorio Americano: un aporte temprano a la gestión del conocimiento - Montero Bustabad, Pedro (2020)
It discusses how the journal Repertorio Americano based on the characteristicsof management defined by Thomas Davenport knowledge activities,conducted a knowledge management in Latin America. Since the late twentiethcentury, the Scriptorium Electronic Library, at Universidad Nacional, isits heir and, makes easy its revitalization.